Police Brutality as Human Rights Violation: A Study Case of Black Lives Matter - Yordan Gunawan; Amarta Yasyhini Ilka Haque; Paul Atagamen Aidonojie (Fakultas Hukum Universitas Muhammadiyah Magelang, 2023)
Today’s unresolved human rights issue is racial misbehavior and police brutality in all of its manifestations. The United States of America stands as a horrifying example of a State that has failed to protect its citizens against bigotry. This has been especially visible in recent years, with several incidents of unjustified police shootings of African-Americans culminating in the formation of the global movement known as “Black Lives Matter,” abbreviated as BLM, which began quietly as a Twitter hashtag. Thus, this study addressed how the legal enforcement against police brutality in the case of Black Lives Matter in the US in regards to human rights violations based on international human rights perspective. The author employed normative research in this study which focuses on library (literature) studies and emphasizes reading and analyzing resources. The result showed that police brutality against Black people is common in the US. Despite the fact that the US has considered regulatory frameworks that establish standards that address discriminatory racial practices in the targeting and killing of unarmed Black boys and men, the implementation of police brutality protection in the US has yet to be effective and thorough. As a result, national action is required to address this issue. There is an urgent need for top management and institutions to step up their supervision of police behavior in order to address the abuse of power by some police forces.